DNA methylation patterns facilitate tracing the origin of neuroendocrine neoplasms - Goeppert, Benjamin; Charbel, Alphonse; Toth, Reka; Zhang, Yue; Tabbakh, Danial; Albrecht, Thomas; Schrimpf, Daniel; de Mestier, Louis; Cros, Jérôme; Vogel, Monika Nadja; Chang, De-Hua; Bohn, Eva-Marie; et al. (Nature Communications, 2025)
Neuroendocrine neoplasms (NEN) are thought to originate from diffuse neuroendocrine networks and therefore most frequently arise in the gastrointestinal tract and lungs. The liver is a frequent site of metastasis of NEN but also the existence of primary hepatic NEN has been proposed. Due to the impact on disease management, it is urgently required to discriminate the origin of hepatic NEN metastases and to identify clinically relevant subgroups. Using a comprehensive set of NEN (N = 212) from two independent cohorts, we show that the DNA methylation profiles of NEN of distinct anatomical localizations differ significantly and primary tumor-metastasis pairs cluster together, enabling the identification of the tumor origin. Furthermore, the subgroup of hepatic NEN without clinically detectable primary tumor, thus classified as primary hepatic NEN, does not form a distinct cluster by DNA methylation analysis but colocalizes with various subgroups of extrahepatic NEN. Organ-specific subtyping of NEN delineates a foregut-like epigenetic profile for hepatic NEN with unknown primary. We propose a classifier with high prediction accuracy for each of the different organ sites. In conclusion, our results demonstrate that DNA methylation profiling enables precise prediction of NEN origin and suggests that a substantial proportion of presumed primary hepatic NEN may in fact represent misclassified secondary hepatic NEN of unknown primary.
Online veröffentlicht: 27. Oktober 2025
Gesehen am 17.12.2025